The effectivity of ultrasound-guided platelet-rich plasma perineural injection in improving leprosy sensory peripheral neuropathy - Brahmanti, Herwinda; Widiatmoko, Arif; Widasmara, Dhelya; Sari, Diane Tantia; Kurniawan, Shahdevi Nandar; Santoso, Widodo Mardi; Laksono, Ristiawan Muji; Gofur, Abdul (UI Scholars Hub, 2023)
Background: Sensory nerve damage is the earliest leprosy sign which can lead to disability. Previous studies showed that autologous platelet-rich plasma (PRP) perineural blind injection can stimulate leprosy sensory nerve regeneration. Our study provided a safer and more accurate PRP agent delivery method through ultrasound-guided injection and was the first to compare PRP versus standard neuropathy treatment, the neurotropic vitamin. This study aimed to determine the effectiveness of combination therapy of ultrasound-guided PRP perineural injection and oral vitamin B complex compared to single oral vitamin B complex in sensory peripheral neuropathy of posterior tibial nerve in leprosy patients.